Effective pedagogical strategies for STEM education from instructors' perspective: OER for educators - Zhu, Meina (Open praxis, 2020)
The Massachusetts Institute of Technology (MIT) OpenCourseWare (OCW) was launched in 2001. It is one of the earliest Open Educational Resources (OER). MIT OCW has published more than 2,400 courses which are available at no cost, the majority of which are STEM related. The purpose of this exploratory study was to examine the pedagogical strategies through reviewing instructor insights of 15 MIT OCW STEM courses using thematic analysis. The most effective pedagogical strategies used found by instructors were active learning, personalizing instruction, engaging learners, providing feedback, building learning community, and clarifying learning objective. Instructors used in-class formative assessment, such as quizzes and oral exams, for just-in-time teaching and online automatic assessment environments for students' self-assessment. The primary summative assessments were final exams and projects. Instructors encountered challenges such as assessing students' learning and changing pedagogical beliefs. Implications for practice were discussed as well.